Projection of Nature in the Śrimad Bhāgavata Mahāpurāna - Pokhrel, Mohan Kumar (JODEM: Journal of Language and Literature, 2020)
mmcjodem98@gmail.com Kṛ ṇa Dvaipāyāna Vyāsa s Śrimad Bhāgavata Mahāpurāna is a reliable text for the projection of Nature. The Nature theory deals with the activities of the Paurānic characters and their love and respect to environment. This study is significant in order to present how Bhāgavata notices the issues on Nature. It traces the far-sightedness of the writer about the condition of Nature despite its writing more than five thousand years before. This analysis is primarily based on Gottfried Wilhelm Leibniz's theory of Nature which confirms the realization of God in Nature and motivates to the readers to love and care Nature as God because of interconnectedness between Nature and life. The researcher has used the English translation of the Sanskrit text of A.C. Bhaktivedānta Svām Prabhupāda. The findings of this investigation endow with the evidences that the text has used the issues on Nature and makes the modern humans aware of the use of Nature maintaining a balance between flora and fauna. The conclusion of the article suggests that Veda Vyāsa is a far-sighted poet of the very ancient time to make to the humans aware of the issues on Nature and motivates them to solve the environmental problems following the advices of the Bhāgavata.